Load Balancing Optimization for Green Cloud Environment Using Effective Scheduling - Sharma, Himanshu; Joshi, Vijay Kumar (International Journal of Intelligent Systems and Applications in Engineering, 2022)
A solution of the green cloud is not only to save the consumption of energy but expressively reduce operational costs. The main objective is to make the comprehensive computing influence of a vast collection of resources offered to a single application. High consumption of energy is the main concern in green cloud computing because of high computations happened in tightly connected data centers that need managed resources and smooth operations. The research is implemented on green cloud computing based on the scheduling process for energy conservation which is the main concern. The groups deal with the high efficient arrangement in which every industry is required with high uniformity, scalability, and effective performance over different cloud computing scenarios. This research work deals with the efficient performance to achieve efficient load balancing and the optimization process for high energy efficiency which will be the key feature of our proposed system. The proposed work deals with the hybrid scheduling process i.e. priority-based weighted round-robin and minimum completion time to reduce the energy consumption in green cloud systems. The performance will be evaluated for low error rates and achieve high energy efficiency to balance loads of the requests.